The problem of “legal bigamy” in the light of the rulings of the District Court in Poznan - Paciorkowski, Szymon (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The purpose of the paper is to present the problem of so-called “legal bigamy” in the light of the rulings of the District Court in Poznan. The marriage law regulations in The Second Polish Republic were completely different in various parts of the country and attempts to unify them failed. This situation caused significant problems: for example, many civil courts refused to recognize some of the divorce judgments issued by church courts in the former Russian partition because of their improper jurisdiction. The paper focuses on two matrimonial cases that were ruled upon by the District Court in Poznan. In both cases the District Court in Poznan was to decide whether divorce judgments issued by the church court of the Polish Orthodox Church in Warsaw were also binding in the former Prussian district.